CSIG-18. MODELING TEMOZOLOMIDE RESISTANCE WITH GLIOBLASTOMA PATIENT DERIVED XENOGRAFTS. (5th November 2018) - James, C David; Ahmed, Atique; Sonabend, Adam; Horbinski, Craig; Stupp, Roger
Abstract: We have conducted experiments with intracranial patient-derived xenograft (PDX) models of glioblastoma (GBM) in which PDX recurrence, following the administration of radiotherapy (RT) and temozolomide (TMZ) to animal subjects, is monitored by bioluminescence imaging. Recurrent tumors were resected from brain then sequentially propagated as subcutaneous xenografts through three successive mouse hosts that received no treatment during tumor propagation. Subcutaneous tumor from the third mouse host was used for establishing intracranial tumors in a new series of mice that received the same treatments as in the initial experiment, in order to assess whether recurrent, treated tumors respond differently to the same treatments used in treating corresponding therapy naïve tumors. We observed no indication of tumor recurring from one cycle of RT + TMZ treatment as displaying resistance to the same treatments used in treating corresponding therapy naïve tumor. However, recurrent tumor that was subjected to two additional cycles of TMZ treatment, prior to resection from brain and subcutaneous propagation through 3 successive mice (107 days total subcutaneous propagation while receiving no treatment), displayed TMZ resistance when tested for response to the same treatments as corresponding naïve tumor. Median TMZ treatment survivals for mice intracranially engrafted with naïve, RT + 1 cycle TMZ treated, and RT + 3 cycles TMZ treated tumor cells were 80, 74, and 42 days, respectively, and survival results yielded log-rank p-values <0.001 for naïve and RT + 1 cycle TMZ comparisons against mice with RT + 3 cycle TMZ treated intracranial tumor. These results suggest that GBM PDX with stable TMZ resistance can be developed in vivo by repetitive, cyclical administration of TMZ to mice with intracranial tumor. Results from the multidimensional analysis of such PDX should yield useful information for testing therapeutic hypotheses aimed at improving treatment outcomes for patients with recurrent GBM.